Factors influencing hearing outcomes in pediatric patients undergoing ossicular chain reconstruction. (August 2017) - Govil, Nandini; Kaffenberger, Thomas M.; Shaffer, Amber D.; Chi, David H.
Abstract: Objective: Ossicular chain disruption in children leads to conductive hearing loss. Few studies have focused on factors influencing successful results in pediatric ossicular chain reconstruction (OCR). We aim to determine whether demographic or surgical factors affect hearing outcomes in pediatric OCR. Methods: We conducted a retrospective chart review of 120 patients undergoing OCR at our institution, a tertiary care hospital, between 2003 and 2014, with median length of follow-up of 2.2 years (range 0.1–9.3 years). Pediatric patients (<18 years old at time of surgical procedure) who had current procedural terminology (CPT) codes of OCR, and available pre- and post-operative audiograms were included in the study. Demographic information, surgical details, and pre- and post-operative pure-tone averages (PTA), speech reception thresholds (SRT), and air-bone gaps (ABG) were recorded from clinic notes, audiograms and operative reports. Differences between PTA, SRT and ABG pre- and post-operatively, as well as demographic and surgical factors, were evaluated using Wilcoxon rank-sum tests. Factors influencing revision were evaluated using Log-rank tests. Results: A total of 120 patients (123 ears) were included. 35.8% of cases were revised, most commonly due to displaced prostheses. 28.5% of surgeries resulted in normal hearing (PTA ≤25 dB) post-operatively. Post-operative SRT and ABG were significantly better in patients with partial ossicular replacement prosthesis (PORP) compared with those with total ossicular replacement prosthesis (TORP) (p = 0.016, 0.027). Titanium prostheses resulted in better post-operative PTA and larger changes in PTA compared with all other materials (p = 0.034, p = 0.038). Conclusions: In our experience, children with titanium prostheses had better hearing outcomes than those with other materials, and children with PORP had better hearing outcomes than those with TORP.